On the Symmetric Block Design with Parameters (306,61,12) Admitting a Group of Order 61 (European Journal of Pure and Applied Mathematics, 2018)
In this paper we have proved that up to isomorphism there are exactly two orbitÂ structures for a putative symmetric block design D with parameters (306,61,12), constructed byÂ group G of order 61. Also the full automorphism groups for these orbit structures are given.
Keywords: Symmetric block design; Orbit structure; Automorphism group